The sum of series involving cosine

  • #1

Homework Statement



Find the sum of the series s(x) = 1 +cos(x)+ (cos2x)/2!+(cos3x)/3!...

Homework Equations





The Attempt at a Solution

 

Answers and Replies

  • #2
gabbagabbahey
Homework Helper
Gold Member
5,002
6
Hi thanksie, what have you tried? What methods have you learned? Are you allowed to compare it to other known series?
 
  • #3
Hi, Yes we can compare it to known series. I've tried a comparison with the harmonic series and the expansion for e^x looks promising. I'm just not sure how to get started.
 
  • #4
gabbagabbahey
Homework Helper
Gold Member
5,002
6
Comparing it to the series for e^x sounds good to me.....try writing [itex]\cos(nx)[/itex] in terms of complex exponentials....what does that give you?
 
  • #5
would x= cosnx? is there a property for cosine where (cos x)^n=cos nx ?
 
  • #6
gabbagabbahey
Homework Helper
Gold Member
5,002
6
would x= cosnx? is there a property for cosine where (cos x)^n=cos nx ?
Not quite...try writing [itex]\cos(nx)[/itex] in terms of complex exponentials....what do you get?
 
  • #7
Do you mean:

x^ni=cos nx + sin nx?
 
  • #8
gabbagabbahey
Homework Helper
Gold Member
5,002
6
Do you mean:

x^ni=cos nx + sin nx?
Huh?!:confused: Why on Earth would you think that were true?

Have you not seen the formulas [tex]e^{i\theta}=\cos\theta+i\sin\theta[/tex] and [tex]\cos\theta=\frac{e^{i\theta}+e^{-i\theta}}{2}[/tex] before?
 
  • #9
sorry i was using that first one. i was confused as to what you meant with cos nx.

using the second one makes a lot more sense. are you saying i should:

cos n(theta) = (e^ni(theta) +e^-ni(theta))/2
 
  • #10
and how do i even find the sum of this series. i only know how to find a sum of a geometric series...i dont know how to deal with the factorial
 
  • #11
gabbagabbahey
Homework Helper
Gold Member
5,002
6
sorry i was using that first one. i was confused as to what you meant with cos nx.

using the second one makes a lot more sense. are you saying i should:

cos n(theta) = (e^ni(theta) +e^-ni(theta))/2
Yes, so now you have

[tex]1+\cos(x)+\frac{\cos(2x)}{2!}+\ldots=\sum_{n=0}^{\infty} \frac{\cos(nx)}{n!}=\frac{1}{2}\sum_{n=0}^{\infty} \frac{e^{i n x}+e^{-i n x}}{n!}[/tex]

correct?

and how do i even find the sum of this series. i only know how to find a sum of a geometric series...i dont know how to deal with the factorial
Try breaking it into two separate sums:

[tex]\frac{1}{2}\sum_{n=0}^{\infty} \frac{e^{i n x}+e^{-i n x}}{n!}=\frac{1}{2}\sum_{n=0}^{\infty} \frac{e^{i n x}}{n!}+\frac{1}{2}\sum_{n=0}^{\infty} \frac{e^{-i n x}}{n!}[/tex]


Now use the fact that [tex]e^{n\theta}=\left(e^{\theta}\right)^n[/tex] and compare each sum to the series for e^u.
 
  • #12
That makes sense. Thanks for all your help.

One more unrelated quick question:
do the series n/(n+1) and n^2/(n^2+1)converge or diverge?
 
  • #13
gabbagabbahey
Homework Helper
Gold Member
5,002
6
do the series n/(n+1) and n^2/(n^2+1)converge or diverge?
Well, try applying some of the convergence tests that you've learned....
 
  • #14
459
0
Huh?!:confused: Why on Earth would you think that were true?

Have you not seen the formulas [tex]e^{i\theta}=\cos\theta+i\sin\theta[/tex] and [tex]\cos\theta=\frac{e^{i\theta}+e^{-i\theta}}{2}[/tex] before?
I looked at this and became interested but got stuck.

[itex] e^{ix} = \cos x + i \sin x [/itex]

[itex] e^{-ix} = \cos x - i \sin x [/itex]

[itex] \cos x = \frac{e^{ix} + e^{-ix}}{2} [/itex]

[itex] \displaystyle\sum_{n=0}^\infty \frac{\cos (nx)}{n!} = \displaystyle\sum_{n=0}^\infty \frac{e^{inx} + e^{-inx}}{2n!} [/itex]

[itex]\displaystyle\sum_{n=0}^\infty \frac{e^{inx} + e^{-inx}}{2n!} = \displaystyle\sum_{n=0}^\infty \frac{e^{inx}}{2n!} + \displaystyle\sum_{n=0}^\infty \frac{e^{-inx}}{2n!}[/itex]

[itex]\displaystyle\sum_{n=0}^\infty \frac{e^{inx} + e^{-inx}}{2n!} = \frac{1}{2} \left[ \displaystyle\sum_{n=0}^\infty \frac{e^{inx}}{n!} + \displaystyle\sum_{n=0}^\infty \frac{e^{-inx}}{n!} \right][/itex]

[itex] e^x = \displaystyle\sum_{n=0}^\infty \frac{x^n}{n!}[/itex]

[itex] \displaystyle\sum_{n=0}^\infty \frac{e^{inx}}{n!} = e^{e^{ix}} [/itex]

[itex] \displaystyle\sum_{n=0}^\infty \frac{e^{-inx}}{n!} = e^{e^{-ix}} [/itex]

[itex]\displaystyle\sum_{n=0}^\infty \frac{e^{inx} + e^{-inx}}{2n!} = \frac{1}{2} \left[e^{e^{-ix}} + e^{e^{ix}} \right] [/itex]

Edit: I think this is OK actually.
 
Last edited:
  • #15
yeah I was going to say that's what I got... lots of thanks to gab, I would have put my work in here but I don't know how to use this forum very well.
 

Related Threads on The sum of series involving cosine

  • Last Post
Replies
4
Views
5K
  • Last Post
Replies
1
Views
2K
  • Last Post
Replies
19
Views
15K
Replies
4
Views
899
Replies
9
Views
1K
Replies
2
Views
1K
  • Last Post
Replies
6
Views
2K
Replies
5
Views
931
  • Last Post
Replies
4
Views
1K
  • Last Post
Replies
1
Views
11K
Top